OPTIMASI KOMPOSISI ETANOL-AIR SEBAGAI CAIRAN PENYARI DALAM PRODUKSI EKSTRAK KERING DAUN SAMBUNG NYAWA [Gynura procumbens (Lour.) Merr.)] - Tantri Lilis Nareswari; Triana Hertiani (Majalah Obat Tradisional, 2016)
Sambung Nyawa leaves (Gynura procumbens (Lour.) Merr has been widely used as herbal medicine which requires a quality improvement of the dry extract for industrial production. Extraction solvent optimization is one key factor which determines the quality. This research aims was to find out the optimal ethanol-water composition as extraction solvent by using Simplex Lattice Design (SLD) method of which the total phenolics, total flavonoids and DPPH radical scavenging activity were used as quality parameters. Dried leaves as raw materials were pulverized and screened at Mesh 60, macerated (1:5) with ethanol-water compositition as 1:0; 0.7:0.3; and 0.5:0.5 v/v, shaked for 24 h, filtered. The procedure was repeated twice. Filtrates were collected of which lactose were added (1:2)w/w and spray dried at 100C for 30 min. Dried extracts yielded were evaluated the quality by using SLD method of which the total phenolics, total flavonoids as well as DPPH radical scavenging activity were used as parameters. Optimal SLD response was revealed at the ethanol:water composition of 0.66:0.34 – 0.75:0.25 v/v (Rtotal>0.9). No significant difference of the above mentioned parameters between the values resulted from the experiment and SLD formula. Correlation analyses of total phenolics and total flavonoids towards DPPH-radical scavenging activity were found as 95.29% and 1.25%, respectively.